Diversity of the calabash tree (Crescentia cujete L.) in Colombia - Arango Ulloa, A.J.; Bohórquez Cháux, Adriana; Duque E., Myriam Cristina; Maass, Brigitte L. (Springer, 2009)
Germplasm of the calabash tree (Crescentia cujete L.) was collected in five major regions of Colombia, i.e. the Andes, Caribbean, Amazon, Orinoco, and Pacific regions. Collecting this multipurpose tree was guided by the indigenous knowledge of farmers and artisans in each region. Large variation in fruit shapes and sizes was found, of which some forms were typical for certain regions. Overall 56 accessions were collected and roughly classified into 22 types by eight fruit shapes and eight sizes. Molecular markers (Amplified fragment length polymorphisms) were applied to leaf tip tissue originating from vegetatively propagated plants in order to assess the diversity available in the germplasm collected as well as to detect patterns of geographical or morphological similarity. One accession each of C. alata H.B.&K. and C. amazonica Ducke were used as outgroups. Overall, genetic diversity was high (mean Nei and Li’s coefficient of 0.43). No relations could be established between either geographical provenance or fruit morphology and patterns of genetic diversity. Concerning the outgroups, the C. amazonica accession appeared to be a distinct species. The C. alata accession, however, did not seem to be sufficiently distinct from C. cujete to merit species status. The latter material may in fact be a hybrid or serve to challenge the validity of interspecific organization of the genus Crescentia.